Ancient CO(2) levels favor nitrogen fixing plants over a broader range of soil N compared to present - Chen, Haoran (Sci Rep, 2021)
Small inreases in CO(2) stimulate nitrogen fixation and plant growth. Increasing soil N can inhibit nitrogen fixation. However, no studies to date have tested how nitrogen fixing plants perform under ancient CO(2) levels (100 MYA), when nitrogen fixing plants evolved, with different levels of N additions. The aim of this study was to assess if ancient CO(2), compared to present, favors nitrogen fixers over a range of soil nitrogen concentrations. Nitrogen fixers (Alnus incana ssp. rugosa, Alnus viridis ssp. crispa, and Alnus rubra) and their close non-nitrogen fixing relatives (Betula pumila, Betula papyrifera, Betula glandulosa) were grown at ancient (1600 ppm) or present (400 ppm) CO(2) over a range of soil N levels, equivalent to 0, 10, 50, and 200 kg N ha(−1) year(−1). The growth of non-N fixing plants increased more than N fixing plants in response to the increasing N levels. When grown at an ancient CO(2) level, the N level at which non-nitrogen fixing plant biomass exceeded nitrogen fixing plant biomass was twice as high (61 kg N ha(−1) year(−1)) as the N level when plants were grown at the ambient CO(2) level. Specific nodule activity was also reduced with an increasing level of soil N. Our results show there was a greater advantage in being a nitrogen fixer under ancient levels of CO(2) compared with the present CO(2) level.